2008
DOI: 10.1007/s10545-007-0786-5
|View full text |Cite
|
Sign up to set email alerts
|

A yeast model reveals biochemical severity associated with each of three variant alleles of galactose‐1P uridylyltransferase segregating in a single family

Abstract: Classic galactosaemia is a potentially lethal inborn error of metabolism that results from profound impairment of galactose-1P uridylyltransferase (GALT). Like many autosomal recessive disorders, classic galactosaemia demonstrates marked allelic heterogeneity; many if not most patients are compound heterozygotes. Owing in part to the fact that most GALT mutations are never observed in patients in the homozygous state, in part to concerns of possible allelic interaction, and in part to the broad range of GALT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…4). The p.Lys285Asn variant, commonly detected in Europeans (33), removes three hydrogen bonds involving helix α 6 , likely destabilising the protein. This agrees with our low recombinant yield for this variant (Supplementary Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). The p.Lys285Asn variant, commonly detected in Europeans (33), removes three hydrogen bonds involving helix α 6 , likely destabilising the protein. This agrees with our low recombinant yield for this variant (Supplementary Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is of note that various cofactors and modifications can alter a metabolic enzyme’s turnover and stability, with functional association to disease (38). As renewed interest in the mechanistic basis of galactosemia has shown that disease-associated mutants exert their effects on misfolding through affecting expression (39), solubility (33,40), stability (31,40,41) and aggregation tendency (31) of hGALT, it is critical to understand the contribution of these factors. The previous lack of consideration of the effects of covalent modification by UMP and divalent metal binding has been in part due to the absence of a crystal structure of the human protein.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast growth assays in the presence of galactose: Yeast growth assays were performed as described previously (Chhay et al 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…2001; Chhay et al. 2008), a characterization of these variants focusing on different structural features is still missing. To date, there is no solved three-dimensional structure of the human GALT.…”
Section: Introductionmentioning
confidence: 99%